Reconceptualizing Inheritance Law in Indonesia’s Islamic Compilation (KHI): A Normative Reassessment Through the Lens of Ibn Mas‘ud’s Jurisprudence - Hafidz, Jibran; Harahap, Muhammad Haikal Khadafi (Sakina: Journal of Family Studies, 2025)
The Compilation of Islamic Law (Kompilasi Hukum Islam, KHI) in Indonesia, particularly in its inheritance provisions, continues to exhibit normative gaps that may result in inequities in the distribution of estates. This study seeks to reconceptualize key aspects of inheritance law in the KHI by drawing on the jurisprudential perspectives of the Prophet’s companion, Ibn Mas‘ud. Using a juridical-normative methodology, enriched with conceptual and comparative approaches, the article examines eight core areas of Islamic inheritance law: the inheritance rights of grandchildren as ashab, the legal position of granddaughters in the presence of daughters or great-grandchildren, the status of consanguine and uterine siblings, inheritance rights of cousins, the application of the radd principle, and the hijab (exclusion) mechanism involving grandfathers. The findings reveal that Ibn Mas‘ud’s reasoning prioritizes substantive justice and maslahah (public interest), diverging from the jumhur ulama who typically adhere strictly to classical doctrines of furudh and qiyas. His approach demonstrates greater adaptability to contemporary socio-legal realities, especially in protecting the rights of heirs who may otherwise be marginalized under a rigid framework. Based on these insights, the article proposes a reinterpretation of several KHI provisions, particularly those concerning heir eligibility, the rights of siblings and cousins, and the standing of grandfathers and granddaughters. This reconceptualization aims to foster an Islamic inheritance law framework in Indonesia that is both doctrinally grounded and socially responsive.